IMPLEMENTATION OF ISLAMIC EDUCATION MANAGEMENT PHILOSOPHY ON THE IMPACT OF FORCED MARRIAGE BY PARENTS ON FAMILY HARMONY - Nurmala Sari, Tanti; Sardimi; Ahmadi; Qalyubi, Imam; Musyarapah (Pena Cendekia Insani, 2026)
This study discusses the implementation of Islamic Education Management Philosophy in addressing forced marriages by parents and their impact on household harmony. This study uses a qualitative approach with data collection using observation, interviews, and documentation to gain an in-depth understanding of religious views, Islamic educational values, and the real experiences of respondents regarding forced marriages. The results show that forced marriage contradicts the principles of Islamic Education Management Philosophy, which emphasizes humanization, justice, deliberation, and respect for individual dignity. The practice of forced marriage has the potential to cause various negative impacts, including domestic disharmony, psychological disorders, poor communication, prolonged conflict, and violations of individual rights. The implementation of Islamic educational values, such as deliberation, compassion, trust, responsibility, and the active role of parents and premarital educational institutions, has proven effective in building individual awareness of the importance of willingness and mental and emotional readiness in choosing a life partner. This study concludes that family education and Islamic education play a strategic role in preventing forced marriage and realizing a harmonious family based on sakinah, mawaddah, and rahmah in accordance with Islamic teachings.